Atomic and Electronic Structure of Metal–Salen Complexes [M(Salen)], Their Polymers and Composites Based on Them with Carbon Nanostructures: Review of X-ray Spectroscopy Studies - Petr M. Korusenko; Olga V. Petrova; Alexander S. Vinogradov (Applied Sciences, 2024)
Currently, electrically conductive polymers based on transition metal complexes [M(Salen)], as well as their composites, are among the systems showing promise as catalysts, electrochromic and electroluminescent materials, and electrodes for energy storage (for batteries and supercapacitors). The current review focuses on elucidating the atomic and electronic structure of metal–salen complexes, their polymers, and composites with nanostructured carbon (carbon nanotubes and graphene) using modern X-ray spectroscopy methods (X-ray photoelectron (XPS) and valence-band photoemission (VB PES) spectroscopy, as well as near-edge (NEXAFS) and extended (EXAFS) X-ray absorption fine structure spectroscopy). We trust that this review will be of valuable assistance to researchers working in the field of synthesizing and characterizing metal–salen complexes and composites based on them.